Customizing Functional Rehabilitation and Return to Sport in the Female Overhead Athlete - Stephanie L. Boudreau, P.T., D.P.T; Laura L. Mattes, P.T., D.P.T., O.C.S; Natalie A. Lowenstein, B.S; Elizabeth G. Matzkin, M.D; Reg B. Wilcox, III, P.T., D.P.T., M.S., O.C.S (Elsevier, 2022)
Participation of female athletes in sports at all levels continues to grow exponentially, as well as the injuries they experience during play. A literature review does outline return to sport guidelines, yet few studies address the potential need for differences between male and female athletes. This commentary is a review of the literature that outlines various sports that involve both male and female overhead athletes and potential differences in upper-extremity injuries and strengths and weaknesses between sexes. This information proposes the potential need to customize return-to-sport guidelines and screens that include recommendations for overhead female athletes within their specific sport, following both injury as well as surgical intervention. Level of Evidence: V.